Quality and quantity of particulate organic Carbon in a coral reef at Tioman Island, Malaysia - Nakajima .R; Yoshida .T; Shibata .A; Othman .B.H.R; Toda .T (Universiti Kebangsaan Malaysia, 2011)
The quality and quantity of particulate organic carbon (POC) were investigated in a fringing coral reef of Tioman Island, Malaysia to better understand the food sources for reef meso-zooplankton. Phytoplankton biomass in the water column was on average 0.22 (± 0.07) mg Chl-a m-3, of which picophytoplankton was the most important (size <3 μm, 50-70% of the total Chl-a). The proportion of C biomass by phytoplankton and other plankton to particulate organic carbon (POC) was low (6% and 5%, respectively) and the major portion of POC was occupied by detritus (89%), suggesting that the diet of particle-feeding or suspension feeding meso-zooplankton would chiefly consist of detritus.